2022
DOI: 10.1371/journal.pone.0274017
|View full text |Cite
|
Sign up to set email alerts
|

Migratory routes, breeding locations and multiple non-breeding sites of Common Whitethroats Curruca communis revealed by geolocators

Abstract: Understanding general migration characteristics and how breeding and non-breeding sites are connected is crucial for predicting the response of long-distance migratory bird populations to environmental changes. We use data collected from six geolocators to describe migratory routes and identify breeding and non-breeding locations, migratory behaviour and differences between spring and autumn migration of Common Whitethroats Curruca communis, an Afro-Palearctic migrant, wintering in Nigeria. Most individuals de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Birds in eastern and southern Africa have been shown to use consecutive sites that sometimes are thousands of km apart (Lack 1986b, Pearson & Lack 1992, Herremans 1998, Jones 1999). However, in the western Sahel birds may remain in the transition zone between desert and the forest, moving a few hundred km southwards in the course of their wintering period, as shown by GPS-equipped European Turtle Doves (Lormée et al 2016, Schumm et al 2021), Montagu's Harriers (Schlaich et al 2016, Schlaich 2019; see also Buij & Croes 2014, for supportive evidence from field observations on a raptor guild in Cameroon) and also by geolocator-equipped birds, such as Common Whitethroat (Tapia-Harris et al 2022), Northern Wheatears (Arlt et al 2015), Tawny Pipits (Briedis et al 2016) and European Turtle Doves (Eraud et al 2013). Bird counts in Nigeria in November, repeated in February, revealed that out of nine migratory species, three had moved southwards and two had moved northwards (Cresswell et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Birds in eastern and southern Africa have been shown to use consecutive sites that sometimes are thousands of km apart (Lack 1986b, Pearson & Lack 1992, Herremans 1998, Jones 1999). However, in the western Sahel birds may remain in the transition zone between desert and the forest, moving a few hundred km southwards in the course of their wintering period, as shown by GPS-equipped European Turtle Doves (Lormée et al 2016, Schumm et al 2021), Montagu's Harriers (Schlaich et al 2016, Schlaich 2019; see also Buij & Croes 2014, for supportive evidence from field observations on a raptor guild in Cameroon) and also by geolocator-equipped birds, such as Common Whitethroat (Tapia-Harris et al 2022), Northern Wheatears (Arlt et al 2015), Tawny Pipits (Briedis et al 2016) and European Turtle Doves (Eraud et al 2013). Bird counts in Nigeria in November, repeated in February, revealed that out of nine migratory species, three had moved southwards and two had moved northwards (Cresswell et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot, however, provide evidence for this, as we do not know whether individuals categorized as “passage” or “unknown” at our study site remained itinerant throughout the season, if they were in fact en route to a stationary nonbreeding site elsewhere, or if they died during the period. These genetic differences could also reflect individuals from different breeding populations, but this seems highly unlikely because individuals switched strategies across years, and Whitethroats seem to have a somewhat low migratory connectivity (Tapia‐Harris et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Short‐term residencies, during both autumn and spring, may indicate the use of multiple important nonbreeding sites. Nigerian Whitethroats deployed with geolocators remained at the first stationary nonbreeding site in the Sahel before arriving at our study site in November (Tapia‐Harris et al, 2022 ). If some of these birds were then to be short‐term residents, individuals could have more than two important stationary nonbreeding sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are six predictions. (1) The Gap of Chad really exists, with lower densities of Eurasian migrants compared to West and East Africa, especially in species which make a detour (Western Bonelli's Warbler; Cramp 1992, Cramp & Perrins 1993, Pilastro et al 1998, Gargallo et al 2011), but (2) the Gap of Chad will be less striking for species which cross the Mediterranean in broad front, such as Common Whitethroat (Tapia-Harris et al 2022), Common Redstart and Woodchat Shrike, if existing at all.…”
mentioning
confidence: 99%